TRIMESTER-SPECIFIC THYROID HORMONE PROFILE OF NORMAL PREGNANT WOMEN OF A NORTH INDIAN CITY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Pregnancy induces significant physiological changes in thyroid function due to hormonal and metabolic demands. Accurate interpretation of thyroid function tests (TFTs) requires trimester-specific and population-specific reference ranges. Aim: To compare thyroid function parameters (TSH, total T3, total T4) between normal pregnant women across trimesters and age-matched non-pregnant women in Jammu, India. Material and Method: A comparative cross-sectional study was conducted at Government Medical College, Jammu, from March 31, 2024, to April 1, 2025. Total 240 participants (60 per group) were enrolled: non-pregnant (Group A), first trimester (Group B), second trimester (Group C), and third trimester (Group D). TFTs were measured using Chemiluminescent Microparticle Immunoassay (CMIA). Results: No significant differences were found in age or BMI across groups. TSH was lowest in the first trimester (0.899 ± 0.33 µIU/mL) and rose progressively to 2.41 ± 0.42 µIU/mL in the third trimester (p < 0.0001). Total T3 peaked in the second trimester (1.95 ± 0.13 ng/dL), while total T4 increased steadily from 8.45 ± 1.02 ng/dL in first to 12.61 ± 1.11 ng/dL in third trimester (p < 0.0001). Compared to non-pregnant values (TSH 2.51 ± 1.51 µIU/mL, T3 1.24 ± 0.24 ng/dL, T4 6.28 ± 1.24 ng/dL), pregnant women showed adaptive euthyroid changes. Overall, thyroid dysfunction prevalence was 36.5%. Conclusion: Significant trimester-specific alterations in thyroid hormones were observed, consistent with physiological adaptations. The findings highlight the need for localized, trimester-specific reference ranges in the Jammu region to improve diagnostic accuracy and maternal-fetal outcomes.